« Le romantique de la clarté » : L’influence de la pensée camusienne sur l’oeuvre de Miklós Mészöly - Radvánszky, Anikó (Verbum – Analecta Neolatina, 2007)
French prose exerted various influences on the Hungarian writer, Miklós Mészöly. The present study focuses on the impact of Albert Camus. The paper interprets the parallelisms of their world-views apparent in their writings, along the lines of the ’light’ motif analysis in The Romanticism of Clarity, an essay by Mészöly on Camus. The light motif guiding the descriptions, based on an accurate perception of the factual world of Mészöly and Camus, does not only shed a light on the possible interpretations of the time concepts the two authors have but also, through the connection of referential representation and ontological/absurd present time, it enables us to gain a deeper insight into the poetics of prose of Mészöly.